Penerapan Qardul Hasan Di Koperasi Syariah Sman 1 Bangkinang Kota - Assyifa, Zubaidah; Winario, Mohd; Hasda, Mifta; Reza, Saru; Zakir, Muhammad; Lismawati, Lismawati; Amelia, Nur (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to analyze the implementation of qardhul hasan in the Sharia Cooperative of SMAN 1 Bangkinang City as a form of financing that is in accordance with sharia principles. Qardhul hasan is a sharia financial product in the form of an interest-free loan that aims to help cooperative members in need. The research method used is a qualitative descriptive approach, with data collection techniques in the form of in-depth interviews, observations, and document studies. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of qardhul hasan in the Sharia Cooperative of SMAN 1 Bangkinang City is in accordance with sharia principles. The loan provision procedure is carried out by considering the eligibility and repayment ability of members, and is equipped with a simple administrative mechanism. In addition, the implementation of qardhul hasan has a positive impact on cooperative members, such as helping urgent needs without burdening interest, and increasing solidarity and a sense of responsibility among members. However, several challenges such as limited funds and member awareness in repaying loans on time need further attention.